An Assessment of Selected Antecedents of Entrepreneurship Intentions and The Level of Entrepreneurial Intention Among Final-Year Undergraduates at The University of Zambia - Mwange, Austin; Chilinda Munthali Muya (Mrs); Marien Matafwali (IJRDO - Journal of Business Management, 2020)
The present study was designed to assess antecedents of entrepreneurship intentions and the level of entrepreneurial intention among final year undergraduates at the University of Zambia. This was a single method descriptive piece of research. An anonymised and self-completing survey questionnaire was distributed to a cross-section of fourth year 2017 final year students of all faculties at the University of Zambia. Data was analysed using SPSS software version 18 (SPSS Inc., Chicago, Illinois, USA). Pearson Chi-square test of significance was used to examine the relationships between the variables. The bivariate correlation coefficients Phi and Cramer V were used to determine the strength and direction. Only n = 136 (30.1%) students out of 452 in the sample were identified as potential entrepreneurs since they intended to start their own businesses. There was a weak significant relationship between entrepreneurial intention and p = 0.001 and phi = 0.317. There was a weak significant relationship between entrepreneurial intention and gender p = 0.001. All schools had more students who intend to work and earn a salary in the public or private sector except the school of veterinary medicine, which had an equal number of students who intend to engage in entrepreneurship activities. None of the schools had the highest proportion of students who had done any topic or a course in entrepreneurship. Generally one can say there was a very low exposure n = 95 (21%) to entrepreneurship education in the university as compared to non-exposure n = 357 (79%). There was no linkage between school and course exposure on entrepreneurship p > 0.05).